2010
DOI: 10.1002/adma.200903193
|View full text |Cite
|
Sign up to set email alerts
|

Organic Semiconductor Growth and Morphology Considerations for Organic Thin‐Film Transistors

Abstract: Analogous to conventional inorganic semiconductors, the performance of organic semiconductors is directly related to their molecular packing, crystallinity, growth mode, and purity. In order to achieve the best possible performance, it is critical to understand how organic semiconductors nucleate and grow. Clever use of surface and dielectric modification chemistry can allow one to control the growth and morphology, which greatly influence the electrical properties of the organic transistor. In this Review, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
425
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(452 citation statements)
references
References 193 publications
8
425
1
1
Order By: Relevance
“…31 During casting and subsequent annealing processes, there is a process of crystallization, alignment of polymer chains, and limited self-organization, which changes the structure to favor exciton collection and charge transport. 50,51 This process is extremely sensitive to the solvent used, 52,53 variations in composition, 54 annealing, [55][56][57][58][59] chemical-structure variations, [60][61][62][63] purities, 64 and processing conditions, 65 to name but a few of the related parameters when dealing with what is a fundamentally unstable system. 66 The seminal work by Yang et al demonstrated the necessity of controlled mixing of the acceptor and donor in the composite.…”
Section: Brief Overview Of Bulk-heterojunction Opvsmentioning
confidence: 99%
“…31 During casting and subsequent annealing processes, there is a process of crystallization, alignment of polymer chains, and limited self-organization, which changes the structure to favor exciton collection and charge transport. 50,51 This process is extremely sensitive to the solvent used, 52,53 variations in composition, 54 annealing, [55][56][57][58][59] chemical-structure variations, [60][61][62][63] purities, 64 and processing conditions, 65 to name but a few of the related parameters when dealing with what is a fundamentally unstable system. 66 The seminal work by Yang et al demonstrated the necessity of controlled mixing of the acceptor and donor in the composite.…”
Section: Brief Overview Of Bulk-heterojunction Opvsmentioning
confidence: 99%
“…2,3,11,14,28 Unfortunately, none of these methods are universally effective and many require numerous processing steps, reducing the cost advantage of solution-processing. Cross-linking reactions permanently alter the chemical structure and generally require chemical tailoring, which usually results in degraded material properties.…”
mentioning
confidence: 99%
“…However, clarifying the detailed, bottom-up relationship between materials and performance has been always challenging since the discovery of semi-conducting conjugated polymers. After the related research for several decades, a great progress has been made in this field [2,3,[19][20][21][22][23][24][25][26][27][28][29], i.e., proposing more clear and efficient synthesis guidelines, concluding principles to improve morphological order and revealing the importance of morphological and structural features in films to the final performance. Now, synthesis of more efficient π-conjugated systems and improvement of order in films have become the essential problems for the development of opto-electronic functional conjugated polymers in terms of chemistry and physics, respectively.…”
Section: Introductionmentioning
confidence: 99%